Impacto de um programa de treino de força com bandas elásticas na aptidão física de atletas de Andebol em cadeira de rodas Roberto António Marto Pereira 2016 - Roberto António Marto Pereira (2016)
Wheechair handball requires maximum efforts and the ability to perform sprints, changes of direction, and shots over long periods. Thus, aerobic capacity and muscular endurance are key skills for performance in this sport. Thus, this study aims to verify the impact of a strength training program with elastic bands on physical fitness of wheelchair handball athletes. The sample was composed by five athletes (♂ = 3; fem. = 2) aged between 28 and 45 years ( ̅= 36 ± SD = 7.6). Four athletes with spinal cord injury and one left leg amputee, All athletes were recruited from the Portuguese Association of Disabled - Delegation of Porto. The athletes were submitted to twelve weeks strength program, using elastic bands, with increments of charge in the fourth and eighth week. The athletes were assessed at baseline and one week after the end of the program. The following instruments were used: the Arm Crank Ergometer, using a respiratory burrows analyzer Cortex: Metalyser 3B, medicine ball 3kg, the Sprint Test 20metros, manual dynamometer, and the one repetition maximum test for the supine chest and back handle.The Student T-Test for paired samples and Wilcoxon test were used for data analysis. Significant differences were found (p <0.05) in the 1RM test in the bench press and chest back puller, 20m sprint test, in VO2 AT test, VO2 AT% test and submaximal VO2 test WattsAT .Although the athletes' output VO2 (i.e., work capacity) did not improved, improvements were found in the strength and speed rates.